A catalog of narrow-line Seyfert 1 galaxies in the southern hemisphere - Chen S.; Berton M.; la Mura G.; Congiu E.; Cracco V.; Foschini L.; Fan J.H.; Ciroi S.; Rafanelli P.; Bastieri D. (Italy, 2026)
We present a new accurate sample of narrow-line Seyfert 1 galaxies (NLS1s) in the southern hemisphere from the Six-degree Field Galaxy Survey (6dFGS). Based on the optical spectral features, 167 sources were classified as NLS1s. We derived flux-calibrated spectra in the sample for the first time. Strong luminosity correlations between the continuum and the emission lines were found. We estimated their central black hole masses and Eddington ratios, which are lying in a typical range of NLS1s. In the sample, 23 NLS1s were detected at radio frequencies and 12 of them are radio-loud. We publish the X-ray data analysis of a campaign of observations carried out by the Swift X-ray Telescope.